Textile Dual Band Circular Ring Patch Antenna under Bending Condition - Isa, M.S.M.; Azmi, A.N.L.; Isa, A.A.M.; M.Zin, M.S.I.; Saat, S.; Zakaria, Z.; Ibrahim, I.M.; Abu, M.; Ahmad, A. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
Textile flexible wearable antenna is becoming a popular study in antenna technology. In this paper, the dual band textile circular patch antenna under bending condition has been designed and analysed. The antenna characteristics such as scattered parameters and radiation pattern has been analysed and compared for normal and bended conditions. Main desired application for the antenna might be on body network which required the wearable condition which incorporated on human torso. The reflection coefficient of the antenna has been determined at 2.4GHz and 5.2GHz which make the antenna to be suitable for WLAN application. To make the antenna suitable to attach on human torso sizes, three bending radii has been chosen, which are 33.5 mm, 47.5 mm and 58.5 mm. The simulated and measured results have been presented and analysed. The antenna with smaller bending radius has shown severe effect on the antenna resonant frequency. However, only slight effect on radiation pattern with compared to the flat antenna. Hence, from the result and analysis, the developed textile antenna is seen to be immune towards the effect of bending and suitable for wearable especial for WLAN application.